Evanescent extraosseous calcifications in low turnover bone: management and outcomes: a case report - Hernandez-Pérez, Mariel; Enos, Daniel (Frontiers in Nephrology, 2026)
IntroductionThe prevalence of bone disease in peritoneal dialysis patients has been recently shown to exceed 54%, including patients with parathormone (PTH) levels within the theoretical adequate target, yet demonstrating low bone turnover on histomorphometry. Moreover, bone disease is often associated with abnormalities in calcium and phosphate metabolism, leading to tissular deposits such as extraosseous calcifications.Case presentationWe present a 22-year-old female patient managed on peritoneal dialysis with persistent swelling of all four extremities, including the fingers, hands, and feet, accompanied by a marked decrease in PTH. Many extraosseous calcifications in the hands were seen in the X-ray images, prompting a switch from peritoneal dialysis to conventional high-flow haemodialysis and intravenous sodium thiosulphate (STS) therapy. The patient showed adequate treatment tolerance, with most calcifications disappearing after 3 months of therapy.ConclusionsOur experience suggests that the treatment of extraosseous calcifications requires timely and multi-angle intervention. At the same time, treatment with STS has proven effective and well tolerated in this patient.